The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1128/mcb.4.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Recessive constitutive mutant Chinese hamster ovary cells (CHO-K1) with an altered A system for amino acid transport and the mechanism of gene regulation of the A system.

Abstract: Chinese hamster ovary cells (CHO-Kl) starved for 24 h for amino acids show a severalfold increase in velocity of proline transport through the A system (Vmax is five times that of unstarved cells). This increase is inhibited by cycloheximide, actinomycin D, N-methyl-a.-amino isobutyric acid (MeAIB, a nonmetabolizable specific A system amino acid analog), and by other amino acids that are generally transported by the A system. However, transport by the A system is not a prerequisite for this repression, and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 13 publications
7
60
1
Order By: Relevance
“…Effect of Derepression on A System Activity and the Na',K+-ATPase. We have previously shown that starving CHO-Ki cells for amino acids that are generally transported by the A system resulted in an increase in A system activity under conditions that required both mRNA and protein synthesis (7). Amino acids that were generally transported by this system, such as proline and MeAIB, acted as co-ri inhibiting the increase in A system activity and associated mRNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect of Derepression on A System Activity and the Na',K+-ATPase. We have previously shown that starving CHO-Ki cells for amino acids that are generally transported by the A system resulted in an increase in A system activity under conditions that required both mRNA and protein synthesis (7). Amino acids that were generally transported by this system, such as proline and MeAIB, acted as co-ri inhibiting the increase in A system activity and associated mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…CHO-K1 (WT), alar4, and WT-alar4 hybrid H3, as well as the medium used in this study, MEMCHO-4, and the culture conditions used have been described (7). Hybrid H4 was isolated previously (7) but was not analyzed at that time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is regulated in vivo and in vitro by both hormonal and nutritional factors [l-3]. System A expression is also regulated at the transcriptional level in cultured cells by amino acid availability, an effect which is called adaptive regulation and involves the de-repression of system A by a putative regulatory gene [4,5]. Also, anisotonic shock seems to selectively induce system A by protein s~thesis-dependent mechanisms which seem to occur through pathways other than the ones involved in adaptive regulation [6,7].…”
Section: Introductionmentioning
confidence: 99%